Seasonal Variation of Enteric Fever in Kathmandu Valley and Antibiotic Susceptibility Profile of Salmonella Enterica - Subedi, Kusum; Gautam, Sushma; Swar, Rajeshwori; Arjyal, Charu; Rijal, Basista Prasad (Tribhuvan University Journal, 2021)
Enteric fever is of public health concern globally, more in the developing countries, which has been causing many morbidity and mortality in low- and middle-income countries. It is mostly related to poor sanitation and contaminated drinking water. This study aims to study the seasonal variation of enteric fever seen in Kathmandu valley and antimicrobial susceptibility profiles of the isolated bacteria. Therefore, blood culture of suspected patients of enteric fever was conducted from April 2018 to April 2020 using standard microbiological techniques; antimicrobial susceptibility testing was performed following Clinical and Laboratory Standard Institute -2017 guidelines. During the study, 104 isolates of Salmonella enteric were isolated, of which Salmonella enterica serovar Typhi were 77.9%, while Salmonella enterica serovars Paratyphi A and B were 21.1% and 1% respectively. Although enteric fever was prevalent throughout the year, the highest number of cases was during the summer. With the increase in temperature, there was also an increase in the cases. Antimicrobial susceptibility profile recorded high resistance of isolates towards Nalidixic acid (97.1%) and Ciprofloxacin (91.3%) while 96% sensitivity to both Ampicillin and Cefixime. This study revealed the occurrence of enteric fever throughout the year, but a large number of cases (51%) are concentrated in the monsoon. Similarly, the resistance of fluoroquinolones reached an alarming state making them inappropriate for use. Ampicillin and Cefixime can be the drug of choice for empirical therapy of enteric fever.